Olga Stanisławska : Une femme seule sur les routes d’Afrique, 1995-1996 - Anna Garycka-Balmitgère (Viatica)
In renewing travel literature, the author-journalist Olga Stanislawska falls within the Polish literary tradition through her travel narrative focused on the African continent: Rondo de Gaulle’a (De Gaulle Roundabout), published in 2001. The study firstly focuses on a presentation of the writer and her first journey to Africa, in the company of two others, followed by an examination of the traveller’s identity crisis, split between her role as a traveller, woman and writer. The emphasis then shifts to the dialogical dimension of the reportage book, as well as the writer’s displacement in the real world, strongly associated with the notion of listening.